Sleep disturbances in patient with chronic nasal obstruction due to nasal polyp: a prospective study - Giri, Dhiraj; Salud, Duane L. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Nasal obstruction is thought to be a major cause of sleep impairment. Typical sleep-related problems seen with nasal polyp include snoring, sleep-disordered breathing and sleep apnoea. The impact of nasal polyposis on quality of life is well studied however its effects on sleep have been less well studied. In the current study, we aim to investigate sleep disturbances in Filipino patients with nasal polyposis using different sleep questionnaires VAS score for snoring, Epworth sleepiness scale (ESS) for daytime sleepiness and Pittsburgh sleep quality index (PSQI) for sleep quality and the effect of endoscopic sinus surgery on sleep quality. Methods: A prospective, non-randomized study was done in the Department of Otorhinolaryngology Head and Neck Surgery of Southern Philippines Medical Center from February 2014 to July 2014. Number of 18 patients with chronic nasal obstruction for more than 6months due to nasal polyps at least grade II on endoscopic examination were included in the study. Visual analogue scale (VAS) score for snoring, ESS for daytime somnolence and PSQI for quality of sleep was compared preoperatively and 1month postoperatively. Results: Mean value of VAS score for snoring, mean value of excessive daytime sleepiness measured by ESS and mean PSQI score for sleep quality improved significantly with p<0.001 after endoscopic sinus surgery. Conclusions: Nasal polyp patients mostly present with nasal obstruction, snoring and excessive daytime sleepiness. Correction of nasal obstruction significantly improves snoring and sleep quality. After endoscopic sinus surgery, patients may experience improvement in snoring and have better sleep quality with decreased daytime sleepiness.